Natural Phenolic Compounds for Health, Food and Cosmetic Applications - Lucia Panzella (MDPI AG, 2020)
Based on their potent antioxidant properties, natural phenolic compounds have gained more and more attention for their possible exploitation as food supplements, as well as functional ingredients in food and in the cosmetic industry [...]